BUDAYA PEMBERIAN KARANGAN BUNGA DALAM ACARA KEMATIAN: KOMPARASI TINJAUAN HUKUM ISLAM DAN SOSIOLOGIS TENTANG FENOMENA SOSIAL - Muchlis Bahar (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2021)
The purpose of this study was to analyze the review of Islamic law regarding the phenomenon of giving wreaths in the event of a death. This study uses a qualitative method with a descriptive sociological approach. The type of data used is secondary data collected through the study of literature and observation of social phenomena. After looking at the description and analysis above, it can be concluded that although sending bouquets of flowers to the bereaved family at the time of death has a good purpose (masyru'), namely to comfort the bereaved family so that they are patient in facing the calamity of death, they are willing to accept the provisions of Allah SWT. However, the procedure is an act that is not prescribed (ghairu masyru'), because what is sent is not to meet food (food) needs. However, on the other hand mafsadat (negative impact) wreaths is quite clear, it is an act of redundancy, sum'ah, riya' and tafakhur (proud) all of which are prohibited by Allah SWT. The positive impact (the element of benefit) is still in doubt. Meanwhile, in the view of Islamic law, this consideration means sending a bouquet of flowers to the bereaved family is Makruh Tahrimiyah, namely an act that is hated, disliked, can lead to an act that is forbidden.